'Good Packaging Can be Misleading'. (24th February 2021) - Ma, James
Abstract : This article explores the applicability of a Peircean approach to the intersubjectivity of adult-child shared reading. Peirce's semiosis serves as an analytical device for ways in which intersubjectivity transcends social interaction. By scrutinising instances of signification, i.e., the production and interpretation of signs constitutive of meaning making in the reading of a dual-language picturebook, the analysis reveals that the word-image complementarity renders an unfolding of intersubjective nuances in collaborative learning and intervention. This provides impetus for furthering Vygotsky's sign mediation to embrace the notion of 'intersemiosis' as indexed to the interdependence of signifying codes in communication and representation, thus theorising how the signification of such codes elicits, invites, and empowers social interaction. Resonant with edusemiotics, increasingly a reference point in the philosophical foundation of learning and development, this article offers pedagogical implications for teachers.